A better way to think about business : how personal integrity leads to corporate success - Solomon, Robert C. (Oxford University Press, 1999)
This work on business ethics for managers is structured around three themes including: the idea that how we perceive and think about organizations we work for is a major factor in the framing and atmosphere of those organizations; and the various business virtues and vices and their role in the daily practice of business.